2020
DOI: 10.46328/ijemst.v8i1.832
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Flipped Mathematics Education by Utilising GeoGebra

Abstract: Combining new educational approaches and educational technologies can make mathematics education more adaptable to pupils’ needs in the 21st century. Our explorative educational study aimed to identify how learning settings and learning environments should be designed to facilitate synthesising flipped approaches to education and using GeoGebra. To discover how to combine flipped approaches and GeoGebra in mathematics education, we conducted a nine-month educational study at a Viennese secondary school. In our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 31 publications
0
14
1
1
Order By: Relevance
“…Around 80% of the students in this research report that they spend the same or less time on flipped homework compared to other subjects. This perception contradicts the findings of research by Muir (2020) and Weinhandl, Lavicza, Hohenwarter and Schallert (2020), with secondary school students and in mathematics classes, who found that using the FC requires more effort from students.…”
Section: Discussioncontrasting
confidence: 83%
“…Around 80% of the students in this research report that they spend the same or less time on flipped homework compared to other subjects. This perception contradicts the findings of research by Muir (2020) and Weinhandl, Lavicza, Hohenwarter and Schallert (2020), with secondary school students and in mathematics classes, who found that using the FC requires more effort from students.…”
Section: Discussioncontrasting
confidence: 83%
“…Many researchers have extensively studied the impact of distance learning on education and have found that distance education has a number of benefits such as ensuring the continuity of education [17,18], ensuring a lifelong learning [19,20], and reducing the high costs associated with traditional education [21]. Limitations such as teaching methods, scheduling, and time have existed since the teacher and the learner were located in different places [22,23].…”
Section: The Impact Of Covid-19 Pandemic On Educationmentioning
confidence: 99%
“…Distance education has many benefits such as ensuring the sustainability of education (Akinbadewa & Sofowora, 2020;Bruder, 1989;Omiles et al, 2019;Seage & Türegün, 2020), providing lifelong learning (Alharthi, 2020;Lou, 2004;Pambayun et al, 2019;Serhan, 2019) and reducing education costs (Al-Husban, 2020; Baggaley, 2008;Hall & Knox, 2009;Harrison & Lee, (2018) although the learner and the teacher are in different places but there are some limitations in terms of methods, schedule and time (Albalawi, 2018;Hannum, 2008;Hilton & Canciello, 2018;Thompson & McDowell, 2019;Uşun, 2006;Vu & Feinstein, 2017;Weinhandl et al, 2020). In addition, many factors such as lack of infrastructure (software, hardware etc.…”
Section: Introductionmentioning
confidence: 99%